2016
DOI: 10.1159/000450640
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Fluency Tasks: Effects of Age, Gender, and Education

Abstract: Objectives: This study presents data for semantic fluency, phonemic fluency, action fluency, and alternate fluency. The aim is to provide normative data by age, gender, and education for European Portuguese in each fluency category. Methods: Norms for the verbal fluency task were collected from a volunteer population of 444 healthy Portuguese participants. Multiple regression analysis with age, gender, and education as independent variables was performed for the semantic fluency global score, and these variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 40 publications
0
22
0
1
Order By: Relevance
“…Other studies also identified the beneficial effect of education on VF. 6,13 To the best of our knowledge, no previous studies specifically focused on the relationship between FRWH and VF tasks performed by MCI and AD older adults with low educational level. The phonemic component of VF was more related to the FRWH than SF, as reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies also identified the beneficial effect of education on VF. 6,13 To the best of our knowledge, no previous studies specifically focused on the relationship between FRWH and VF tasks performed by MCI and AD older adults with low educational level. The phonemic component of VF was more related to the FRWH than SF, as reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The educational level played an important role on the performance of all VF tasks, influencing ten out of the 25 variables analyzed, such as the number of switches and phonemic clusters for PF, and the number of switches, taxonomic clusters, and mean cluster size for SF. Santos Nogueira et al 13 also identified a positive effect of education on VF, suggesting that it compensates for age-related decline.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Le et al, 2018). As semantic verbal fluency is associated with age (Clark et al, 2009;Santos Nogueira, Azevedo Reis, & Vieira, 2016), the failure to adjust for age may have obscured a significant effect. Alternatively, these previously reported non-significant correlations could be explained by the use of composite measures of both phonemic and semantic fluency as we did not find strong evidence for a relationship between phonemic verbal fluency and brainPAD (although it was significant in DEU, this correlation was not replicated in CR/RANN).…”
Section: Semantic Verbal Fluencymentioning
confidence: 99%
“…Age-and-schooling-adjusted normative, clinical and population data are available for the total number of the names generated in a minute in the Spanish language 11 - 16 and age-, sex- and schooling-adjusted normative data are also available in the Portuguese language. 17 Nevertheless, performance of this task is influenced by age and schooling, among other variables. 18 Researchers have suggested that schooling is possibly the sociodemographic factor that have the greatest influence on verbal fluency scores.…”
mentioning
confidence: 99%